2010
DOI: 10.1227/neu.0b013e3181fa00f1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nuclear Factor κB in Cerebral Arteriovenous Malformations

Abstract: We detected activation of NF-κB in the endothelium and perivascular infiltrating inflammatory cells within the cerebral AVM nidus, suggesting a role in the pathophysiology of cerebral AVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The IMIDs do not inhibit endothelial cell proliferation, but rather, migration [148, 149]. There is a remarkable overlap in the pathways targeted by IMIDs in neoplastic disorders [144] with those dysregulated in bAVM, e.g., NFκB activation [94], VEGF overexpression [66], HIF-1α [150], αvβ3 [67, 151], and cytokine elaboration [105], including TNF-α [152] and IL-1β [153]. Both thalidomide and lenalidomide improved outcomes and reduced TNF-α and IL-1β expression in an amyotrophic lateral sclerosis mouse model [154, 155], suggesting that the drug can cross the blood-brain barrier in a setting with some impairment of barrier integrity like our bAVM model [65].…”
Section: New Therapeutic Targetsmentioning
confidence: 99%
“…The IMIDs do not inhibit endothelial cell proliferation, but rather, migration [148, 149]. There is a remarkable overlap in the pathways targeted by IMIDs in neoplastic disorders [144] with those dysregulated in bAVM, e.g., NFκB activation [94], VEGF overexpression [66], HIF-1α [150], αvβ3 [67, 151], and cytokine elaboration [105], including TNF-α [152] and IL-1β [153]. Both thalidomide and lenalidomide improved outcomes and reduced TNF-α and IL-1β expression in an amyotrophic lateral sclerosis mouse model [154, 155], suggesting that the drug can cross the blood-brain barrier in a setting with some impairment of barrier integrity like our bAVM model [65].…”
Section: New Therapeutic Targetsmentioning
confidence: 99%
“…Moreover, we reported that the death receptor pathway and the NF-kappaB pathway were upregulated in AVMs. 9 , 11) These results indicate that dynamic vascular remodeling and neuronal death occur in and around the nidus of AVMs. 16 20) The majority of these studies, however, have focused on only one or a few genes or protein products.…”
Section: Discussionmentioning
confidence: 74%
“… 5 8) Moreover, we have reported that AVM lesions display DNA fragmentation and increased expression of apoptosis-related factors. 9 11) In this study, we examined differential gene expression in AVMs and analyzed this expression in relation to clinical manifestations in Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, immune cells were mostly analyzed in ruptured [24] and irradiated [25] bAVMs. Our previous study showed that adaptive immune cells were rarely observed in unruptured bAVM.…”
Section: Discussionmentioning
confidence: 99%